2011
DOI: 10.1111/j.1365-2133.2011.10591.x
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian target of rapamycin (mTOR) inhibitors slow skin carcinogenesis, but impair wound healing

Abstract: This case impressively illustrates the clinical dilemma for mTOR inhibitor use where benefit in carcinogenesis is counterbalanced by impairment in wound healing. Changes in immunosuppressive regimens should thus be made on an individual basis with careful consideration of the relative risks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 13 publications
1
23
0
2
Order By: Relevance
“…These data suggest that different extracellular stimuli require various degrees of threshold Akt kinase activity for signaling. Furthermore, our findings in this study also connect well with those in several recent reports showing that the downstream effect of Akt, the mTOR pathway, plays an essential role in wound healing (33)(34)(35)(36)(37)(38). Therefore, taking all this together, it is becoming clear that the eHsp90␣-subdomain II of LRP-1-NPVY motif-Akt1/2-mTOR pathway represents a new therapeutic target for skin wound healing.…”
Section: Discussionsupporting
confidence: 75%
“…These data suggest that different extracellular stimuli require various degrees of threshold Akt kinase activity for signaling. Furthermore, our findings in this study also connect well with those in several recent reports showing that the downstream effect of Akt, the mTOR pathway, plays an essential role in wound healing (33)(34)(35)(36)(37)(38). Therefore, taking all this together, it is becoming clear that the eHsp90␣-subdomain II of LRP-1-NPVY motif-Akt1/2-mTOR pathway represents a new therapeutic target for skin wound healing.…”
Section: Discussionsupporting
confidence: 75%
“…Despite this wealth of in vitro data, relatively little is known about the in vivo requirement of actomyosin contractility for desmosomal adhesion and epidermal barrier formation. mTOR signaling perturbation in the epidermis has previously been associated with epithelial carcinogenesis (30), epidermal stem cell senescence (31,32), and delayed wound healing (33). While this article was in preparation, an additional study demonstrated that mTOR kinase and mTORC1 loss of function is associated with impaired epidermal differentiation and barrier formation; however, the molecular mechanism of this finding was not elucidated, and no effects on cell-cell adhesion were described (34).…”
Section: Introductionmentioning
confidence: 77%
“…Tolerability of mTORI, particularly their tendency to cause mouth ulcers and rashes, has prevented their wider use [100,101]. The other area where mTORI may have a role is in the management of transplant patients who develop a malignancy, since both sirolimus and everolimus, like other mTORI, have been shown to have anti-neoplastic properties [102].mTORI impair wound healing and, while this might be anticipated to be most important around the time of transplant, it can be a significant problem if patients develop neuropathic ulcers in their post transplant period since these will be slower to heal and, indeed, maybe exacerbated by the mTORI with devastating results [103].…”
Section: Maintenance Therapymentioning
confidence: 99%